Analysis of High Molecular Mass Compounds from the Spider Pamphobeteus verdolaga Venom Gland. A Transcriptomic and MS ID Approach (2021)
Nowadays, spider venom research focuses on the neurotoxic activity of small peptides. In this study, we investigated high-molecular-mass compounds that have either enzymatic activity or housekeeping functions present in either the venom gland or venom of Pamphobeteus verdolaga. We used proteomic and transcriptomic-assisted approaches to recognize the proteins sequences related to high-molecular-mass compounds present in either venom gland or venom. We report the amino acid sequences (partial or complete) of 45 high-molecular-mass compounds detected by transcriptomics showing similarity to other proteins with either enzymatic activity (i.e., phospholipases A2 , kunitz-type, hyaluronidases, and sphingomyelinase D) or housekeeping functions involved in the signaling process, glucanotransferase function, and beta-N-acetylglucosaminidase activity. MS/MS analysis showed fragments exhibiting a resemblance similarity with different sequences detected by transcriptomics corresponding to sphingomyelinase D, hyaluronidase, lycotoxins, cysteine-rich secretory proteins, and kunitz-type serine protease inhibitors, among others. Additionally, we report a probably new protein sequence corresponding to the lycotoxin family detected by transcriptomics. The phylogeny analysis suggested that P. verdolaga includes a basal protein that underwent a duplication event that gave origin to the lycotoxin proteins reported for Lycosa sp. This approach allows proposing an evolutionary relationship of high-molecular-mass proteins among P. verdolaga and other spider species.